Biofabrication of Zinc Oxide Nanoparticles With Syzygium aromaticum Flower Buds Extract and Finding Its Novel Application in Controlling the Growth and Mycotoxins of Fusarium graminearum - Lakshmeesha, Thimappa Ramachandrappa; Kalagatur, Naveen Kumar; Mudili, Venkataramana; Mohan, Chakrabhavi Dhananjaya; Rangappa, Shobith; Prasad, Bangari Daruka; Ashwini, Bagepalli Shivaram; Hashem, Abeer; Alqarawi, Abdulaziz A.; Malik, Jahangir Ahmad; Abd_Allah, Elsayed Fathi; Gupta, Vijai Kumar; et al. (Frontiers in Microbiology, 2019)
Fusarium graminearum is a leading plant pathogen that causes Fusarium head blight, stalk rot, and Gibberella ear rot diseases in cereals and posing the immense threat to the microbiological safety of the food. Herein, we report the green synthesis of zinc oxide nanoparticles from Syzygium aromaticum (SaZnO NPs) flower bud extract by combustion method and investigated their application for controlling of growth and mycotoxins of F. graminearum. Formation of SaZnO NPs was confirmed by spectroscopic methods. The electron microscopic (SEM and TEM) analysis revealed the formation of triangular and hexagonal shaped SaZnO NPs with size range 30–40 nm. The synthesized SaZnO NPs reduced the growth and production of deoxynivalenol and zearalenone of Fusarium graminearum in broth culture. Further analysis revealed that treatment of mycelia with SaZnO NPs resulted in the accumulation of ROS in the dose-dependent manner. Also, SaZnO NPs treatment enhanced lipid peroxidation, depleted ergosterol content, and caused detrimental damage to the membrane integrity of fungi. Moreover, SEM observations revealed that the presence of diverged micro-morphology (wrinkled, rough and shrank surface) in the macroconidia treated with SaZnO NPs. Taken together, SaZnO NPs may find a potential application in agriculture and food industries due to their potent antifungal activity.